RISK MANAGEMENT IN THE DIGITAL ERA ADDRESSING CYBERSECURITY CHALLENGES IN BUSINESS - Djajasinga, Nico Djundharto; Fatmawati, Endang; Syamsuddin, Syamsuddin; Sukomardojo, Tekat; Sulistyo, Arif Budi (Branding: Jurnal Manajemen dan Bisnis, 2023)
In the rapidly evolving digital landscape, businesses face unprecedented cybersecurity challenges that pose significant risks to their operations and data integrity. This study aims to explore effective risk management strategies tailored to the unique demands of the digital era, focusing on mitigating cybersecurity threats in the business sector. Through a comprehensive analysis of current cybersecurity trends, threats, and the efficacy of various risk management frameworks, this research offers insights into developing robust defense mechanisms against cyber threats. The methodology encompasses a mixed approach, combining qualitative and quantitative data from industry case studies, expert interviews, and cybersecurity incident reports. The findings reveal a pressing need for adaptive risk management strategies that are proactive, resilient, and aligned with the evolving nature of cyber threats. The study concludes with actionable recommendations for businesses to enhance their cybersecurity posture, emphasizing the integration of advanced technological solutions, employee training, and a culture of security awareness. This research contributes to the field by providing a nuanced understanding of cybersecurity challenges in the business context and proposing a comprehensive framework for effective risk management in the digital era.